Rhizospheric Bacterial Community of Endemic Rhododendron arboreum Sm. Ssp. delavayi along Eastern Himalayan Slope in Tawang - Debnath, Rajal; Yadav, Archana; Gupta, Vijai K.; Singh, Bhim P.; Handique, Pratap J.; Saikia, Ratul (Frontiers in Plant Science, 2016)
Information on rhizosphere micobiome of endemic plants from high mountain ecosystems against those of cultivated plantations is inadequate. Comparative bacterial profiles of endemic medicinal plant R. arboreum Sm. subsp. delavayi rhizosphere pertaining to four altitudinal zonation Pankang-Thang (PTSO), Nagula, Y-junction and Bum La (Indo-China border) (in triplicates each) along cold adapted Eastern slope of Himalayan Tawang region, India is described here. Significant differences in DGGE profile between below ground bulk vs rhizospheric community profile associated with the plant was identified. Tagged 16S amplicon sequencing from PTSO (3912m) to Bum La (4509 m), revealed that soil pH, total nitrogen (TN), organic matter (OM) significantly influenced the underlying bacterial community structure at different altitudes. The relative abundance of Acidobacteria was inversely related to pH, as opposed to TN which was positively correlated to Acidobacteria and Proteobacteria abundance. TN was also the significant predictor for less abundant taxonomic groups Chloroflexi, Gemmatimonadetes and Nitrospirae. Bum La soil harbored less bacterial diversity compared to other sites at lower altitudes. The most abundant phyla at 3% genetic difference were Acidobacteria, Actinobacteria and Proteobacteria amongst others. Analysis of similarity indicated greater similarity within lower altitudinal than higher altitudinal group (ANOSIM, R = 0.287, p = 0.02). Constraining the ordination with the edaphic factor explained 83.13% of variation. Unique phylotypes of Bradyrhizobium and uncultured Rhizobiales were found in significant proportions at the four regions. With over 1% relative abundance Actinobacteria (42.6%), Acidobacteria (24.02%), Proteobacteria (16.00%), AD3 (9.23%), WPS-2 (5.1%) and Chloroflexi (1.48%) dominated the core microbiome.